2022
DOI: 10.1186/s40795-022-00625-5
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to low carbohydrate diets and non-alcoholic fatty liver disease: a case control study

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is defined as the excessive accumulation of fat in the liver cells of people who do not drink alcohol. The aim of study is investigated the association between low carbohydrate diets (LCDs) and NAFLD. Methods This age and gender-matched case–control study was conducted on 120 patients newly diagnosed with NAFLD and 120 adults without NAFLD. Diagnosis of NAFLD based on laboratory tests and abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…(2) Studies on the treatment of NAFLD. Many pieces of evidence showed that calorie restriction ( 18 , 19 ), fat restriction ( 20 , 21 ), carbohydrate reduction ( 22 , 23 ), and appropriate vitamin supplementation ( 24 , 25 ) in diet therapy, aerobic exercise ( 26 , 27 ) resistance exercise ( 28 , 29 ) and high-intensity interval training ( 30 ) in exercise therapy had good therapeutic effects. Moreover, clinical experiments have proved that combining diet and exercise may achieve better therapeutic efficacy than a single one ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Studies on the treatment of NAFLD. Many pieces of evidence showed that calorie restriction ( 18 , 19 ), fat restriction ( 20 , 21 ), carbohydrate reduction ( 22 , 23 ), and appropriate vitamin supplementation ( 24 , 25 ) in diet therapy, aerobic exercise ( 26 , 27 ) resistance exercise ( 28 , 29 ) and high-intensity interval training ( 30 ) in exercise therapy had good therapeutic effects. Moreover, clinical experiments have proved that combining diet and exercise may achieve better therapeutic efficacy than a single one ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%